Temporal Change of Land Use /Land Cover (LULC) Over a Decade (2005-2016) in Jamnagar Municipal Corporation, Gujarat, India - Yadav, Rajkumar; Patel, Nitin; Gohil, Mitesh; Sugoor, R.K. (Indian Forester, 2022)
The Jamnagar city in Gujarat state is one of the important industrial hub which has shown changes in Land Use/Land Cover (LULC) along with time. In the current study, the LULC changes of Jamnagar Municipal Corporation (JMC) have been assessed and understood over a decade (2005-2016). During the study, whole area of JMC was classified into 4 categories i.e.open tree coves, built-up area, open land and water bodies based on remote sensing data. The interpretation and analysis of study showed that open tree cover got increased by 73.45 ha from 486.66 ha in 2005 to 560.11 ha in 2016, while, the open land area has declined by 613.90 ha from 11237.93 ha in 2005 to 10624.03 ha in 2016 which probably got converted into the built-up area which showed an increase of 565.25 ha from 1034.17 ha in 2005 to 1599.42 ha in 2016. Moreover, the water body area has also changed drastically across the years and declined by 24.80 ha from 88.24 ha in 2005 to 63.44 ha in 2016. This information of different land categories of JMC can be used in town planning and land administration of Jamnagar city in sustainable manner.